Design of mold press for the manufacturing of silica sand pellet form - Dedikarni Panuh; Rieza Zulrian Aldio; Amir Surya Hidayah (Jurnal Litbang Industri, 2021)
Currently, the ceramic industries is utilizing many natural mineral resources. The purpose of this study is to design and manufacture the tool; a mold press pellet or silica sand mold  and to obtain the results of silica sand pellets that are affected by varying pressure. The materials used for the tools were STM A276, Type 410 steel. ST60 martensite. SS400 steel was used to made the round plate at a mold position. This study produced mold with dimensions of 25.45 mm of diameter, height of 89 mm, volume at 45.07 cm³ with a mold circle area of 5.06 cm² and punch cross-sectional area of 452.16 mm². The maximum pressing force on the mold was 49050 N, the normal stress result was 108.47 MPa, the strain value was 3.8 mm / mm, the modulus of elasticity value was 28.54 MPa, the mold material had a maximum limit of 812,871 MPa, indicating that the mold material used was very good. This silica sand pellet mold produced can be utilized for the development of fuel cell and composite materials.